An investigation into the effects of the epidermal growth factor receptor tyrosine kinase inhibitor "Gefitinib" on human breast cancer - Gutteridge, Eleanor (2010)
Background. In vitro studies have shown that ER+ acquired tamoxifen resistant MCF7 breast cancer cell lines can show elevated levels of EGFR expression with an increase in its subsequent signalling pathway(s) and that these are growth inhibited by gefitinib, an EGFR tyrosine kinase inhibitor. This thesis examines the effect of gefitinib on tamoxifen resistant human breast cancer in the clinical setting and in an ‘in-vivo’ mouse model. Patients and Methods. This phase 2 clinical study recruited 54 patients. 28 were oestrogen receptor positive and had progressed on tamoxifen treatment(acquired resistance), the other 26 (48.1%) were oestrogen receptor negative(de novo resistance). Patients were given a loading dose of 1000mg gefitinib on Day 1 and then gefitinib 500mg as a once daily oral dosing until evidence of disease progression. Clinical data were recorded. Sequential tumour biopsies were taken pre-treatment, after 8 weeks therapy and at the development of resistance and analysed immunocytochemically to identify predictive factors for response to treatment and also to see the effect of treatment and resistance on tumour biology, encompassing monitoring steroid receptors, EGFR, HER2 and IGFR, downstream kinases MAPK and AKT, and the proliferation marker Ki67. In parallel with the clinical study, ER+ acquired tamoxifen resistant MCF7 xenografts (TAMR) were grown in nude mice in the presence of tamoxifen and treated with gefitinib 50mg per day orally (designated 3 treatment) or tamoxifen alone (designated control) and monitored for impact on tumour growth. Results. In the phase 2 study gefitinib treatment was well tolerated with an overall clinical benefit rate of 33.3% (n=18/54). Pre-treatment oestrogen receptor positivity was associated with tumour response to gefitinib (p=0.015, longer TTP (p = 0.015), and with clinical benefit (CB) in 53.6 % of the ER+ acquired tamoxifen resistant patients. In contrast, the clinical benefit rate was minimal in the steroid receptor negative patient cohort (11.5%). All patients in this series expressed detectable levels of EGFR, but high pre-treatment levels of EGFR predicted a poorer outcome (p=0.075) Only patients achieving CB had a significant fall in Ki67 staining as measured at 8 weeks versus pretreatment levels (p=0.024), and that Ki67 levels were lower in CB than PD patients at this time. We observed lower levels of EGFR phosphorylation at this time point in some CB patients. Further examination of the CB pts who showed a >10% decline in EGFR phosphorylation revealed decreases in phosphorylation of MAPK and also in Ki67. TAMR xenografts expressed high levels of EGFR as previously observed in vitro. Their growth was significantly inhibited by gefitinib (p=0.039) over the study period while after only 2 weeks of gefitinib treatment tumours showed a decrease in the level of Ki67 staining (p = 0.068). Conclusion. Acquired tamoxifen resistance in vivo both in patients and in a xenograft model appears to be in part mediated through EGFR pathway signalling and this can be blocked and growth inhibited with gefitinib. In ER 4 negative tumours the effects of gefitinib were less striking, suggesting alternative signalling pathways are dominant in promoting their growth despite obvious overexpression of EGFR.